PENDUGAAN STOCK KARBON TERSIMPAN PADA MODEL MANAJEMEN HUTAN MERANTI DI KAWASAN SUNGAI PENITI BESAR PROVINSI KALIMANTAN BARAT - Saputra, Hendra; Hardiansyah, Gusti; Fahrizal, . (Universitas Tanjungpura, 2018)
The estimation of carbon stocks is very important in providing information about the amount of carbon that is generated in the land sector in Global Warming. The objective of this research is to know carbon stock from Above Ground Biomass in Tree stands in a Development Area the Hutan Merati Forest Management Unit (PMUMHM) located in the district of Landak and district in West kalimantan province with 2,637,58 hectares. The method of calculating the estimation of stored carbon stock is done by non-destructive (Non-destructive) and using allometric equations. The allometric equation Manuri at all, 2014 (y = 0.232. (DBH) 2,373. (WD) 0.736) is because this model is very conservative and relevant to field conditions after being tested with some other allometric equations. The results of this study show that the stored biomass of 597.29 Ton/Ha with the amount of carbon stored for 246,089.86 Ton/Ha. and produce carbon dioxide uptake of 903,149.79 TonCO2/Ha and produce Oxygen of 334.159,99 TonO2/Ha. And if this area is maintained until the year 2030 can save the carbon of 665,905.36 Ton/Ha. Keywords: Allometrik, Biomass, Carbon Dioxide, Oxygen